JURIDICAL ANALYSIS OF INHIBITING FACTORS LAW ENFORCEMENT IN HANDLING OF ACTIONS THE CRIMINAL CRIMINAL OF COOKING OIL embezzlement (Number : 2557//Pid.B/2022/PN.Mdn.) MEDAN STATE COURT - Mahzaniar; Prasetiyo (Fox Justi : Jurnal Ilmu Hukum, 2023)
Abstract Embezzlement is an act of dishonesty by hiding other people's goods/ property by one or more people without the knowledge of the owner of the goods with the aim of transferring property (theft), possession, or use for other purposes. The criminal act of embezzlement is regulated in Article 372, Article 374, and Article 375 of the Penal Code. The definition of embezzlement is regulated in Article 372 of the Criminal Code. In this study, the author wants to discuss how the Juridical Analysis of Law Enforcement Inhibiting Factors in Handling Cooking Oil Embezzlement Crime (Number: 2557//Pid.B/2022/ Pn.Mdn.) Medan District Court. In this study the author used explanatory qualitative research methods. Research does not simply describe the occurrence of phenomena but tries to explain why the phenomenon occurs and what influences it has to provide an explanation for why something happens. In this study, it was found that the defendants were legally and conclusively proven guilty of committing the crime of "embezzlement because there is a continuous employment relationship" as stipulated in Article 374 jo. Article 64 of the Penal Code with imprisonment for 1 (one) year and 6 (six) months minus